Repetisi mengenai Keputusasaan Pemazmur dalam Menantikan Pertolongan Allah: Eksegesis Mazmur 13: A Repetition of the Psalmist's Despair in Waiting for God's Help: Exegesis of Psalm 13 - Farel Yosua Sualang; Jani (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Psalm 13 is a repetition which ends by moving to serenity as part of God's help. The method used is qualitative with a hermeneutic approach, especially poetry Genre. This study aims to explain a repetition of the psalmist as an emphasis on supplication to God which has an impact on theological values. This article finds the psalmist's complaint three times repeated; first, the expression of the psalmist's long-suffering despair, the second the psalmist sincerely hoped for deliverance from God which could soon be realized. Then there is a repetition of the salvation of God Himself, who saves from the world of death, illuminates the eyes (verse 3), and the third does good things (v. 5b).